Modified quantitative systems theoretic accident model and processes (STAMP) analysis: A catastrophic ship engine failure case. (1st June 2022) - Ceylan, Bulut Ozan; Akyuz, Emre; Arslanoğlu, Yasin
Abstract: Despite the rapid advancement of technology and the increasing complexity of systems, conventional accident analysis techniques developed many years ago are still used in numerous sectors. On the other hand, these approaches are limited in detecting all underlying causes of accidents in complex socio-technical systems. In recent years, system theory-based novel accident analysis techniques have been proposed to address this issue. Systems-Theoretic Accident Model and Processes (STAMP) is one of these innovative analytic techniques with a strong detection capability. The method has the ability for analyzing human, organization, hardware, software, external factor components, and their interactions in a dynamic structure. However, despite the method's strong analysis capacity, it is a shortcoming that STAMP is a qualitative method. This study aims to present a hybrid quantitative methodology for complex system accidents based on a system engineering perspective to fill this gap. In this context, a real catastrophic marine diesel engine incident was analyzed to prove the applicability and effectiveness of the methodology. According to the analysis results, the main causes of the case incident were systematically determined as 80% human factor, 13% hardware & software factor, and 7% external factor. Highlights: A modified methodology for complex process accident analysis based on a system engineering perspective is presented. The proposed methodology is based on STAMP and rule-based fuzzy FMEA approaches. A real catastrophic engine failure is chosen to show the implementation of the intended methodology. The main reasons of the M/V Guroni Incident are due to 80% human, 13% hardware & software, and 7% external factors.